2017
DOI: 10.1021/acs.estlett.7b00352
|View full text |Cite
|
Sign up to set email alerts
|

Submicrometer Particles Are in the Liquid State during Heavy Haze Episodes in the Urban Atmosphere of Beijing, China

Abstract: The particle phase state is a key factor for determining gas particle partitioning, particle reactive gas uptake, and multiphase chemical reactions, with associated links to secondary aerosol formation. In this study, the particle phase state was investigated by measuring particle rebound fraction f in the highly polluted atmosphere of Beijing, China. The particle phase state was sensitive to ambient relative humidity (RH). The particles changed from rebounding to adhering when the RH increased above 60%, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
158
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(176 citation statements)
references
References 39 publications
14
158
4
Order By: Relevance
“…In this study we assume that the bulk diffusivity within organic particles is independent of particle mixing state and morphology. Chamber experiments have demonstrated that evaporation of organic aerosol may be hindered if it is coated with organic aerosol from a different precursor (Loza et al, 2013;Boyd et al, 2017). Moreover, the phase separation has been observed in organic particles mixed with inorganic salts (You et al, 2014) and even without inorganic salts (Pöhlker et al, 2012;Riedel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this study we assume that the bulk diffusivity within organic particles is independent of particle mixing state and morphology. Chamber experiments have demonstrated that evaporation of organic aerosol may be hindered if it is coated with organic aerosol from a different precursor (Loza et al, 2013;Boyd et al, 2017). Moreover, the phase separation has been observed in organic particles mixed with inorganic salts (You et al, 2014) and even without inorganic salts (Pöhlker et al, 2012;Riedel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Such variations are overall consistent with our previous results in winter of 2011-2012 . A recent study found a clear transition of particle phase state from solid/semisolid to liquid at RH = 40-60% (Liu et al, 2017), which might also facilitate the rapid increases in this RH range. In comparison, the variations of aerosol species are relatively small at high RH levels (60-80%), and the concentrations are consistently high in both winters.…”
Section: Chemically Resolved Pm Pollutionmentioning
confidence: 99%
“…Aerosol liquid water (ALW) is a ubiquitous component of ambient aerosol and exerts great influences on aerosol physical and chemical properties, especially in regions with high relative humidity (RH) (Cheng et al, , 2008Covert et al, 1972;Ervens et al, 2014;Nguyen et al, 2016;Pilinis et al, 1989;Wu et al, 2018;Zheng et al, 2015). From the perspective of aerosol physical processes, ALW influences particle lifetime, optical properties, radiative forcing, and the ability of particles to deposit in the humid human respiratory tract (Andreae and Rosenfeld, 2008;Cheng et al, 2008;Covert et al, 1972;Löndahl et al, 2008). ALW also promotes partitioning of some of the inorganic gases and water-soluble organic gases to the condensed phase, thus directly increasing aerosol mass loadings (Asa-Awuku et al, 2010;Parikh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(1) aerosol mass loadings increase significantly, (2) particle phase changes from solid/semisolid to liquid phase (Liu et al, 2017), (3) both sulfur and nitrogen oxidation ratios increase Sun et al, 2013;Zheng et al, 2015), (4) water-soluble inorganics increase faster than organics Quan et al, 2015;Sun et al, 2013;Zheng et al, 2015). RH affects secondary species via heterogeneous uptake or aqueous processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation